Overview of the national bank of Romania's role in the last century - Adina Criste; Iulia Lupu (Financial Studies, 2020)
The central bank is one of the main pillars of a country's government and one of the institutions most required to respond to crisis situations in the economy. In this respect, the National Bank of Romania, as the monetary authority of the Romanian state, is constantly subject to such pressure. The article aims to highlight the role that the monetary authority in Romania has had over a century since the Great Union. The research is based on the analysis of some historical documents that testify the major changes through which had passed this institution, as well as the remarks noted lately, especially after Romania's accession to the European structures. The results obtained give a general picture reflecting the role of the National Bank of Romania policy over a century filled with social, political and economic events.
Keywords: N14; E31; E58; 330; monetary unification; monetary reform; currency regime; anti-inflationary policies